IMPLEMENTASI MODEL CSR PADA UMKM BINAAN BANK BPD DIY - Dhyah Setyorini; Amanita Novi Yushita; Sukirno Sukirno; Endra Murti Sagoro (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
The purpose of this study was to find out the CSR model (specifically the development of MSMEs) at Bank XYZ and develop the XYZ-guided Bank SME CSR model to increase the productivity of XYZ-assisted MSMEs. Based on the documentation, observations and in-depth interviews with informants, the results show that the CSR model implemented at XYZ Bank is technically charged with implementation on certain function lines, no task force that handles CSR programs. This research also results in the development of a CSR model by modifying the previous model.